Peranan LAZISNU Sidoarjo dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat di Kabupaten Sidoarjo - Al Faruq, Muhammad; Muhammad Hamdan Ali Masduqie; Umi Julaihah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The economic welfare of the people in Indonesia is arguably still very low. According to the Central Statistics Agency (BPS), the average data for poor households in Indonesia is 4.74 people. And in the province of East Java, the average data for poor households is in first place reaching 4.181 million people. While the majority of the population in Indonesia is Muslim. The National Zakat Amil Agency (BAZNAS) estimates that the potential for Zakat, Infaq, Alms and Waqf (ZISWAF) in Indonesia reaches more than 500 trillion rupiah. In fact, in the next 5 years it is expected to collect a total of ZISWAF reaching 50-60 trillion rupiah through collaboration with Bank Syariah Indonesia (BSI). The purpose of this study is to find out how the role of LAZISNU Sidoarjo is in improving the economic welfare of the people in Sidoajo Regency. This research method uses a qualitative approach. Data collection techniques in this study were obtained through observation, interviews and documentation. Observations were made to find out the general description and situation or conditions in the field at the philanthropic institution. Interviews were conducted using source triangulation techniques to obtain data validity through LAZISNU Sidoarjo administrators and mustahik or recipients of assistance from the Zakat, Infaq and Shadaqah (ZIS) distribution program that had been carried out. The data analysis technique in this study was through data reduction, data presentation and data verification. The results of this study indicate that with a consumptive and productive assistance program, mustahik feel very happy and happy. Because the funds and capital obtained are able to help mustahik in meeting the necessities of life and business development that will and has been going on for that long. This success is also inseparable from the ZIS management mechanism that has been implemented by LAZISNU Sidoarjo including planning, organizing, implementing and supervising. So that the role of LAZISNU Sidoarjo in Improving the Economic Welfare of the Community in Sidoarjo Regency has been running effectively and efficiently.